Diagnostic yield of electromagnetic navigational bronchoscopy: A safety net community-based hospital experience in the United States - Sujith V Cherian; Saranjit Kaur; Siddharth Karanth; Jonathan Z Xian; Rosa M Estrada-Y-Martin (Annals of Thoracic Medicine, 2021)
INTRODUCTION: Electromagnetic navigational bronchoscopy (ENB) is an excellent tool to diagnose peripheral pulmonary nodules, especially in the setting of emphysema and pulmonary fibrosis. However, most of these procedures are done by interventional pulmonologists and academic tertiary centers under general anesthesia. Studies evaluating the diagnostic utility of this tool in safety-net community hospitals by pulmonologists not formally trained in this technology are lacking. The objective was to evaluate the diagnostic yield of ENB done in such a setting and its associated complications. METHODS: Retrospective chart review of consecutive ENB procedures over 5 years from 2014, since its inception in our institution-a safety-net community based hospital was performed. Multiple variables were analyzed to assess their impact on diagnostic yields. RESULTS: After exclusion criteria were applied, 72 patients with 76 procedures were eventually included within our study, with an overall 1-year diagnostic yield of 80.2%. Sensitivity for malignancy was 73% and negative predictive value of 65%. Primary lung cancer was the most common diagnosis obtained, followed by tuberculosis (TB). The overall complication rates were low, with only 1 patient (1.3%) requiring hospitalization due to pneumothorax needing tube thoracostomy. No deaths or respiratory failures were noted within the cohort. The only significant variable affecting diagnostic yield was forced expiratory volume in 1 s. The presence of emphysema did not affect diagnostic yield. CONCLUSIONS: ENB is safe and feasible with a high diagnostic success rate even when performed by pulmonologists not formally trained in interventional pulmonology in low resource settings under moderate sedation.